Comparison of different cephalometric variables in patients with and without history of snoring - Khan, Azhar; Imran, Mohamad; Imran, Mohammed; Parkar, Shoib N.; Islam, Mueed U.; Nazir, Shayan (International Journal of Research in Medical Sciences, 2017)
Background: Obstructive sleep apnea syndrome has a high prevalence among adults. Cephalometric variables can be a valuable method for evaluating patients with this syndrome. The objective of this study is to evaluate and compare the craniofacial variables in subjects with and without snoring by cephalometric analysis. Methods: 40 patients were included in the study who were divided into two groups; group 1 of 20 snoring patients and group 2 control group of 20 non-snoring patients and were evaluated and compared for various cephalometric variables. Results: The distance from the hyoid bone to the mandibular plane (MP-H) was the only variable that showed a statistically significant correlation between two groups. Conclusions: Cephalometric variables are useful tools for evaluating the patients with snoring who are predisposed to obstructive sleep apnoea. The distance from the hyoid bone to the mandibular plane showed a statistically significant correlation between two groups.